2016
DOI: 10.1155/2016/8173905
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Branched-Chain Amino Acids, Metabolic Syndrome, and Cardiovascular Risk Profile in a Chinese Population: A Cross-Sectional Study

Abstract: Objective. This study aimed to evaluate the relationship between branched-chain amino acids (BCAAs), metabolic syndrome (MS), and other cardiovascular (CV) risk factors in middle-aged and elderly Chinese population at high risk for the development of cardiovascular disease (CVD). Methods. 1302 subjects were enrolled from the Huai'an Diabetes Prevention Program. Results. BCAAs levels were positively correlated with MS, its components, and CV risk profile. The odds ratio (OR) for MS among subjects in the fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
(51 reference statements)
2
40
0
Order By: Relevance
“…Hence, the rate of brain histidine uptake via this transporter should be proportionate to the plasma ratio of histidine to the sum of other neutral amino acids; this sum is determined primarily by BCAA levels. This observation may be pertinent to cross-sectional studies concluding that plasma levels of BCAAs are elevated in those with type 2 diabetes, metabolic syndrome and/or obesity 35–40. Moreover, several prospective studies have found that plasma levels of BCAAs likewise correlated positively with type 2 diabetes risk 41–43.…”
Section: Interaction With Branched-chain Amino Acids (Bcaas)mentioning
confidence: 75%
“…Hence, the rate of brain histidine uptake via this transporter should be proportionate to the plasma ratio of histidine to the sum of other neutral amino acids; this sum is determined primarily by BCAA levels. This observation may be pertinent to cross-sectional studies concluding that plasma levels of BCAAs are elevated in those with type 2 diabetes, metabolic syndrome and/or obesity 35–40. Moreover, several prospective studies have found that plasma levels of BCAAs likewise correlated positively with type 2 diabetes risk 41–43.…”
Section: Interaction With Branched-chain Amino Acids (Bcaas)mentioning
confidence: 75%
“…Obesity may track more strongly than metabolic syndrome and diabetes with elevated BCAA . In a study of 1302 people aged 40–79; higher levels of BCAA tracked with older age, male sex, and metabolic syndrome, as well as with obesity, cardiovascular risk, dyslipidemia, hypertension, and uric acid . Medium‐ and long‐chain acylcarnitines, by‐products of mitochondrial catabolism of BCAAs, as well as branched‐chain keto acids and the BCAA themselves distinguished obese people having versus not having features of IR, and in a study of 898 patients with essential hypertension, the BCAA and tyrosine and phenylalanine were associated with metabolic syndrome and impaired fasting glucose .…”
mentioning
confidence: 99%
“…Another study showed that plasma phenylalanine, together with branched chain amino acids (BCAAs), has a positive association with both systolic and diastolic BP [ 72 ]. Regarding BCAAs, the results are conflicting: dietary BCAAs have been shown to be not associated [ 73 ], positively associated [ 70 ], or even negatively associated [ 74 ], with the risk of hypertension. Probably because of the varying study populations used and the differences in the study design and end points, there was little consistency among the BCAAs reported to be associated with the risk of hypertension.…”
Section: Amino Acids and Hypertensionmentioning
confidence: 99%